2019
DOI: 10.1080/00036846.2019.1701181
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting core inflation: the case of South Africa

Abstract: Forecasting and estimating core inflation has recently gained attention, especially for inflation targeting countries, following research showing that targeting headline inflation may not be optimal; a Central Bank can miss the signal due to the noise. Despite its importance there is sparse literature on estimating and forecasting core inflation in South Africa, with the focus still on measuring core inflation. This paper emphasises predicting core inflation using large time-varying parameter vector autoregres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…Their findings suggest that the locally linear model tree provides forecasts that can compete with the linear autoregressive model and is generally superior over longer horizons. In addition, Ruch et al (2020) derive forecasts for quarterly measures of core inflation in South Africa with the aid of time-varying parameter vector autoregressive models (TVP-VARs), factor-augmented VARs, and structural break models to show that small TVP-VARs outperform all their other models, where additional information on the growth rate of the economy and the interest rate is sufficient to forecast core inflation accurately.…”
Section: Review Of Inflation Forecasting In South Africamentioning
confidence: 99%
“…Their findings suggest that the locally linear model tree provides forecasts that can compete with the linear autoregressive model and is generally superior over longer horizons. In addition, Ruch et al (2020) derive forecasts for quarterly measures of core inflation in South Africa with the aid of time-varying parameter vector autoregressive models (TVP-VARs), factor-augmented VARs, and structural break models to show that small TVP-VARs outperform all their other models, where additional information on the growth rate of the economy and the interest rate is sufficient to forecast core inflation accurately.…”
Section: Review Of Inflation Forecasting In South Africamentioning
confidence: 99%
“…That is why academia, policy makers, and other concerned stakeholders conduct ex ante or ex post research to investigate theses structural changes in numerous financial and economic variables. Ruch et al (2020), Anguyo et al (2020), Hegerty (2020), Nath and Sarkar (2019), Gil-Alana (2019), Orlowski (2017) examine the break dates and the impact of structural changes on inflation series with regards to other variables. Ruch et al (2020) predict inflation variables using factor-augmented VARs (FAVAR), time-varying parameter vector autoregressive models (TVP-VARs), and structural break models.…”
Section: Literaturementioning
confidence: 99%
“…Ruch et al (2020), Anguyo et al (2020), Hegerty (2020), Nath and Sarkar (2019), Gil-Alana (2019), Orlowski (2017) examine the break dates and the impact of structural changes on inflation series with regards to other variables. Ruch et al (2020) predict inflation variables using factor-augmented VARs (FAVAR), time-varying parameter vector autoregressive models (TVP-VARs), and structural break models. They found that models with heteroscedastic errors performed better than models with homoscedastic errors.…”
Section: Literaturementioning
confidence: 99%
“…Franz et al [17] compared time-varying parameter VAR, factor-augmented VAR and structural break models to analyze core inflation in South Africa using quarterly data from 1981Q1 to 2013Q4. The study showed time varying parameter model having consistence performance over constant coefficient model.…”
Section: Introductionmentioning
confidence: 99%